Perceptions of The Teachers Teaching Styles Variants on National Income Materials In Sekolah Penggerak - Kurniawan, Achmad Adi; Andriansyah, Eka Hendi (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research aims to analyze the joint influence of student perceptions regarding teaching style variants. interactional teachers on student learning outcomes on national income material at driving schools. The population of 3 high schools with driving school status in Gresik Regency was 432, then a simple random sampling technique was used. The sample used in this research was 144 students using explanatory quantitative methods and using tests, hypotheses, classical assumptions, multiple linear regression analysis. Based on the results of data processing, a coefficient of determination (R-squared) of 0.64 was obtained. Thus, it can be concluded that the combined influence of variables X on variable Y is 64%, while 36% is caused by the influence of other variables. Thus, it is hoped that schools will hold teacher training to improve teachers' varied teaching abilities so that student learning outcomes are optimal.